WIDENING ECONOMIC DISPARITIES IN INDIA: CHALLENGE FOR INCLUSIVE DEVELOPMENT - Yadav, Dr. Anil Kumar (Research Parks Publishers, 2020)
The Indian growth story has been far from perfect. That is not an understatement by any stretch of imagination. A growing challenge for the economy is the fast-evolving problem of inequality. Most recently, James Crabtree in his latest book,